The Exegesis of Woman Leadership According to 1 Corinthians 11:2-16 - Hannas Hannas; Rinawaty Rinawaty (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2018)
The role of woman until now still encounters various problems, such as in the leadership. Do women have decent capacity to lead, or they are on second class under men. This research, brings up to the readers the original understanding about the role of woman especially in leadership. To see woman leadership, the researchers using exegesis method by utilizing four Bible analysis, these are: contextual analysis, syntactical analysis, verbal analysis, theological analysis, and homiletical analysis. Study which was done toward this research found out that woman essential leadership is how the man and woman aware that leadership which is designed by God, the Creator, is leadership based on function, where the man and the woman realize their roles and function corresponding with God’s created nature. Man are leader, who lead with obedience and love. Whereas woman are under man’s authority who has to be followed with respect and full of love.